2014
DOI: 10.1515/cclm-2013-0976
|View full text |Cite
|
Sign up to set email alerts
|

System accuracy evaluation of systems for point-of-care testing of blood glucose: a comparison of a patient-use system with six professional-use systems

Abstract: Data from this study, which focused on system accuracy, suggest that SMBG systems can achieve system accuracy that is comparable with professional-use systems when measurements are performed on capillary blood samples by trained personnel in a standardised and controlled setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 26 publications
1
22
0
Order By: Relevance
“…With the increase in BG concentrations, the rate of discrepancy increased. The result is contradicted with those of Guido et al , who indicated that the POCT system meet the criteria of the ISO 15197:2013 standard. In order to ensure that POCT can be more effectively applied to auxiliary diagnosis, the operators should fully understand the factors affecting the detection results.…”
Section: Discussionmentioning
confidence: 63%
“…With the increase in BG concentrations, the rate of discrepancy increased. The result is contradicted with those of Guido et al , who indicated that the POCT system meet the criteria of the ISO 15197:2013 standard. In order to ensure that POCT can be more effectively applied to auxiliary diagnosis, the operators should fully understand the factors affecting the detection results.…”
Section: Discussionmentioning
confidence: 63%
“…Waist-to-height ratio was calculated as waist circumference (cm) divided by height (cm). Biochemical measurements were performed on finger-prick blood samples using validated dry chemistry methods (AccuChek AVIVA, Roche Diagnostics S.p.A., Mannheim, Germany for glucose and MultiCare-in, HPS, Italy, for total cholesterol and triglycerides) [25, 26]. Nonfasting participants were asked to return at fast for blood tests.…”
Section: Methodsmentioning
confidence: 99%
“…For BGMS in current use, the ISO 2003 standards were those that had to be met. In fact, the accuracy and performance of BGMS used globally today, both professional and self-monitoring systems, have been assessed in multiple studies, demonstrating their adherence to ISO standards in effect at that time, as previous studies have reported [4][5][6][7][8][9]. New and more stringent ISO standards were introduced in 2013 (ISO 15197: 2013) [3].…”
Section: Introductionmentioning
confidence: 99%